Static friction on a ball rolling down an incline. (14th September 2018) - Cross, Rod
Abstract: A ball that rolls without sliding down an inclined plane requires a small static friction force to prevent the ball sliding down the incline. The magnitude of that force is investigated by considering the force needed to prevent the contact point from slipping.